The Use of Soetji Nurani Temple in Introducing Tolerance as a Social Value - Karina Muthia Mursid; Ersis Warmansyah Abbas; Mutiani Mutiani (Universitas Lambung Mangkurat, 2023)
This service aims to analyse the Existence of the Soetji Nurani Temple in Banjarmasin. In line with the purpose of the service, the service method uses outreach to the broader community as a form of the Existence of the Soetji Nurani Temple. Data was collected using observation techniques and interviews and supported by sources of information from books and journals. The subjects in this dedication were the temple administrators and several community leaders. The dedication results show that the Soetji Nurani Temple is a historic building and a Cultural Heritage in Banjarmasin. The existence of this building has a significant influence on the surrounding community, especially as a tourist attraction. Viewed from the peak of the Chinese New Year celebrations, the Soetji Nurani Temple is a target for tourists and Chinese citizens to carry out worship, religious activities, and traditional medicine from both local and foreign areas.